Role of peptidoglycan in the pathogenesis of Staphylococcus saprophyticus in mice (Baghdad Science Journal, 2025)
The pathogenicity of S. saprophyticus was studied in mice. A group of white mice were injected transurethrally using a catheter with S. saprophyticus S67 cell suspension in a concentration reached 109 CFU/ml. concomitantly, the role of its peptidoglycan in the pathogenicity was studied by injecting another group of mice with 0.3 mg/0.2 ml of partially purified S. saprophyticus S67 peptidoglycan extract. After autopsy, kidneys and urinary bladder showed several histopathological changes both in cells and peptidoglycan injected mice, included: hydropic degeneration, glomerulus shrinkage, congestion of renal vessels, infiltration of inflammatory cells, and dekeratinization in urinary bladder.